2018
DOI: 10.1016/j.whi.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Pregnancy Intention, Reproductive Coercion, and Partner Violence among Family Planning Clients: A Qualitative Exploration

Abstract: Racial differences exist in experiences of IPV/RC with regard to UIP even among women with similar economic resources and health care access. These findings provide much-needed context to the persistent racial/ethnic disparities in UIP and illustrate influences beyond differential access to care and socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 44 publications
1
52
1
1
Order By: Relevance
“…Estimates suggest that 2.4% or almost 2.9 million U.S. women overall reported RRP during their lifetime. In contrast to other studies that have found racial/ethnic disparities in rape victimization 20,21 and reproductive coercion and UIP, 18,19 in this national sample the authors found similar RRP prevalence across racial/ethnic groups. Findings reveal that IPs are common perpetrators of RRP.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Estimates suggest that 2.4% or almost 2.9 million U.S. women overall reported RRP during their lifetime. In contrast to other studies that have found racial/ethnic disparities in rape victimization 20,21 and reproductive coercion and UIP, 18,19 in this national sample the authors found similar RRP prevalence across racial/ethnic groups. Findings reveal that IPs are common perpetrators of RRP.…”
Section: Discussioncontrasting
confidence: 99%
“…Although this is a nationally representative sample with respect to age and race/ethnicity, previous studies used clinical samples focusing on a cohort of women having a racial/ethnic distribution dissimilar to that of the U.S. adult population. 18,19 In addition, qualitative studies suggest that there are nuanced racial/ethnic differences in the experiences of reproductive coercion and IPV and the mediators with UIP, 17,19 which may not be captured in the measures used in this study. It could also be that SES is playing a role, given some previous work has found racial/ethnic differences associated with IPV are reduced when social class is controlled.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The discussion extended beyond the circumstances in which women became mothers. Once motherhood was achieved, the role of women was the primary, if not exclusive, caregiver to their children . The assumption that a woman must care for her children when fathers are absent or abusive was nearly universally stated among participants.…”
Section: Resultsmentioning
confidence: 99%